2018
DOI: 10.1002/prca.201700090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of p90 Ribosomal S6 Kinase 2 as a Novel Host Protein in HBx Augmenting HBV Replication by iTRAQ‐Based Quantitative Comparative Proteomics

Abstract: PurposeThe aim of this study was to screen for novel host proteins that play a role in HBx augmenting Hepatitis B virus (HBV) replication.Experimental designThree HepG2 cell lines stably harboring different functional domains of HBx (HBx, HBx‐Cm6, and HBx‐Cm16) were cultured. ITRAQ technology integrated with LC‐MS/MS analysis was applied to identify the proteome differences among these three cell lines.ResultsIn brief, a total of 70 different proteins were identified among HepG2‐HBx, HepG2‐HBx‐Cm6, and HepG2‐H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Several studies indicated that HBx causes hepatic steatosis in hepatocyte mediated by transcriptional activation of sterol regulatory element-binding protein 1 (SREBP1) and peroxisome proliferator-activated receptor gamma (PPARγ). Our previous study also demonstrated that HBx related differentially expressed proteins are associated with lipid metabolism 27 . HBx induces abnormal lipid metabolism to meet the bioenergetic demands of extreme cell growth and proliferation 28,29 .…”
Section: Discussionmentioning
confidence: 76%
“…Several studies indicated that HBx causes hepatic steatosis in hepatocyte mediated by transcriptional activation of sterol regulatory element-binding protein 1 (SREBP1) and peroxisome proliferator-activated receptor gamma (PPARγ). Our previous study also demonstrated that HBx related differentially expressed proteins are associated with lipid metabolism 27 . HBx induces abnormal lipid metabolism to meet the bioenergetic demands of extreme cell growth and proliferation 28,29 .…”
Section: Discussionmentioning
confidence: 76%
“…Members of RSK family contained RSK1, RSK2, RSK3, and RSK4. Among them, activated RSK2 was shown to phosphorylate several transcription factors response to viral infection (Yan et al 2018). Surviladze et al (2013) revealed that activation of PI3K/Akt/mTOR could phosphorylate S6K to further activate the downstream signal pathways in response to human papillomavirus type 16 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on yeast proteomics, Zeyen et al (2020) found that hepatitis B subviral enveloped particles utilize the coat protein complex II component for intracellular transport by selectively utilizing Sec24A and Sec23B. Based on isobaric tags for relative and absolute quantitation (iTRAQ) quantitative comparative proteomics, RSK2 was identified as a novel host protein that plays a role in HBx enhancing HBV replication (Yan et al, 2018). Using the substrate capture proteomics, Murphy et al (2016) showed that the main function of HBx is to degrade SMC5/6, which can suppress HBV replication by inhibiting HBV gene expression.…”
Section: Proteomicsmentioning
confidence: 99%